Ramadan Fasting in Kidney Transplant Recipients: A Single-Centre Retrospective Study - Ihab A. Ibrahim; Ehab A. Hassan; Abdelrahman M. Alkhan; Mohamed A. Hussein; Ahmed F. Alhabashi; Tariq Z. Ali; Yasir Z. Shah; Ibrahim S. Alahmadi; Mohamed S. Abdelsalam; Mohamed E. Rashwan; Ammar Abdulbaki; Dieter C. Broering; et al. (Journal of Transplantation)
Background. Fasting during the lunar month of Ramadan is mandatory to all healthy adult Muslims. Renal transplant recipients are often worried about the impact of fluid and electrolyte deprivation during fasting on the function of their allograft. We aimed to examine the effect of fasting Ramadan on the graft function in renal transplant recipients. Methods. This retrospective cohort study included patients who underwent kidney transplantation in our tertiary referral center. Baseline pre-Ramadan estimated glomerular filtration rate (eGFR), mean arterial pressure (MAP), and urinary protein excretion were compared to those during and after Ramadan within and between the fasting and non-fasting groups. Results. The study population included 280 kidney transplant recipients who chose to fast during the Ramadan month (June-July 2014) and 285 recipients who did not fast. In the fasting group, baseline eGFR did not change from that during or post-Ramadan (72.6±23.7 versus 72.3±24.5 mL/min/1.73 m2, P=0.53; and 72.6±23.7 versus 72±23.2 mL/min/1.73 m2, P=0.14, respectively). Compared to baseline, there were no significant differences between the fasting and the non-fasting groups in terms of mean percent changes in eGFR, MAP, and urinary protein excretion. Conclusion. Fasting during the month of Ramadan did not have significant adverse effects on renal allograft function.